Disentangling occupation- and sector-specific technological change - Zsófia L. Bárány; Christian Siegel (Institute for Advanced Studies (IHS), 2017)
Occupational and sectoral labor market patterns display a significant overlap. This implies that economic models can explain these patterns to a large degree through either sector- or occupation-specific technological change, but stay silent about the level of specificity. We propose a model where technologies evolve at the sector-occupation level, allowing us to extract sector-only and occupation-only components and to quantify their importance. We find that most of productivity changes are occupation-specific, but that there is also a sizable sector component. We contrast the data and our baseline model against implications of models where technological change is restricted to be either at the sector or at the occupation level, or both. All three restricted models can replicate both sectoral and occupational outcomes very well, but occupation-specific changes are crucial for within-sector changes of occupational employment and income shares.
Keywords: 330